Memory and mineness in personal identity. (18th May 2016) - Roache, Rebecca
Abstract: Stanley Klein and Shaun Nichols (2012) describe the case of patient R.B., whose memories (they claim) lacked the sense of "mineness" usually conveyed by memory. Klein and Nichols take R.B.'s case to show that the sense of mineness is merely a contingent feature of memory, which they see as raising two problems for memory-based accounts of personal identity. First, they see it as potentially undermining the appeal of memory-based accounts. Second, they take it to show that the conception of quasi-memory that underpins many memory-based accounts is inadequate. I argue that Klein and Nichols' characterization of R.B.'s experience is implausible; as a result, the problems that they describe for memory-based accounts of personal identity do not arise.